2016
DOI: 10.1021/acs.energyfuels.6b00112
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Low-Temperature Mass-Transfer Properties of Methane and Carbon Dioxide in n-Decane, Hexadecane, and Bitumen Using the Pressure-Decay Technique

Abstract: The pressure-decay technique is used to determine the diffusivity and solubility of methane and carbon dioxide in pure hydrocarbons and bitumen at temperatures of 0, 15, 20 and 25 °C and pressure of 3.5 MPa. An analytical-graphical technique is implemented to extract the related mass-transfer parameters, i.e., diffusion coefficient and Henry's constant, from the pressuredecay data. The results reveal that the diffusion coefficient of methane and carbon dioxide in both, pure hydrocarbons and bitumen, decreases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Upreti and Mehrotra [ 21,22 ] considered concentration‐dependent diffusivity, D = D ( w ), in the primary mass transfer model (Equation ()), and reported the diffusivity of several gases in heavy oils using the principles of variational calculus. Based on analytical solutions of the mass transfer model, Zhang et al, [ 23 ] Sheikha et al, [ 24,25 ] and Pacheco‐Roman et al [ 26 ] developed graphical techniques to determine gas diffusivity from pressure decay data. Tendulkar et al [ 27 ] and Kundra et al [ 28,29 ] extended this approach to gas‐polymer systems.…”
Section: Methods For Diffusivity Determinationmentioning
confidence: 99%
“…Upreti and Mehrotra [ 21,22 ] considered concentration‐dependent diffusivity, D = D ( w ), in the primary mass transfer model (Equation ()), and reported the diffusivity of several gases in heavy oils using the principles of variational calculus. Based on analytical solutions of the mass transfer model, Zhang et al, [ 23 ] Sheikha et al, [ 24,25 ] and Pacheco‐Roman et al [ 26 ] developed graphical techniques to determine gas diffusivity from pressure decay data. Tendulkar et al [ 27 ] and Kundra et al [ 28,29 ] extended this approach to gas‐polymer systems.…”
Section: Methods For Diffusivity Determinationmentioning
confidence: 99%
“…This result means that the diffusion of CO 2 in the oil-saturated core is dramatically enhanced by the increasing temperature. Additionally, as the viscosity of oil decreases with the increase of temperature (as shown in Figure b), the diffusivity of CO 2 increases with the decrease of viscosity. , The diffusion process on the molecular scale depends primarily on the movement of molecules of gas amongst oil molecules. Because the motion of gas molecules increases with temperature, the kinetic energy of the gas molecule increases as well.…”
Section: Resultsmentioning
confidence: 94%
“…Nikkhou et al [2] reported the diffusion coefficient of CO 2 in heptane and hexadecane, deduced from the swelling of pendant drops at T = (313 to 393) K and pressures up to 8.6 MPa. Pacheco-Roman et al [3] used the pressure-decay method to determine the diffusivity of CO 2 in decane and hexadecane at T = (273 to 298) K and at p = 35 MPa. Additional data for CO 2 in hexadecane have been reported by Du et al [4] and Hao et al [5] using the Dynamic Pendant Droplet Volume Analysis (DPDVA) method and the NMR method, respectively.…”
Section: Introductionmentioning
confidence: 99%